Comparative analysis of probe‐based ramp metering with detector‐based and pretimed ramp metering. Issue 1 (11th April 2012) - Kattan, Lina; Saidi, Saeid
SUMMARY: In this paper, a probe‐based adaptive ramp metering approach has been developed and compared with a detector‐based and pretimed ramp metering approaches using PARAMICS microsimulation model made by Quadstone Limited. Both examined probe‐based and detector‐based ramp metering approaches adopt the same problem formulation; however, they differ by the data source that provides estimates of their input parameters. The probe‐based approach takes as main input space mean speed extracted from vehicle probes moving constantly on the entire freeway. The detector‐based approach takes the density readings directly from point detectors placed upstream and downstream of each on‐ramp. The developed approach formulates the ramp metering rates to simultaneously reduce freeway travel time and decrease delays on ramps. A dynamic weighting scheme is adopted in this formulation to give different weighting schemes to the various freeway sections and the on‐ramps. These weights are able to adjust dynamically based on prevailing and forecasted traffic conditions to give priority in each step to the sections of the freeways or/and on‐ramps experiencing critical traffic conditions. The comparative analysis of the three ramp metering approaches was conducted on an 8‐km freeway section on Highway 2 in Calgary, Alberta, Canada. The results of the analysis indicate that the probe‐based algorithm consistently outperformed the two other approaches in terms of all performance measures. The probe‐based approach is shown to exceed the performance of the detector‐based approach with a market share of vehicle probes as low as 3%. The results of the analysis are promising and show the effectiveness of developing ramp metering control algorithms taking the main input parameters from vehicle probes on the freeway. Copyright © 2012 John Wiley & Sons, Ltd.